Hoitotyön johtamisen tehtävänkuvat ja johtamisosaaminen jatkuvan oppimisen opintokokonaisuuteen osallistuvilla opiskelijoilla - Terkamo-Moisio Anja; Leino-Kilpi Helena; Kaakinen Pirjo; Palonen Mira; Peltonen Laura-Maria; Vaartio-Rajalin Heli; Häggman-Laitila Arja (Hoitotieteiden tutkimusseura HTTS r.y., 2022)
The future changes in social- and health care require renewing and strong leadership skills as well as continuous learning from the health care leaders. The aim of this study was to describe the work descriptions and leadership skills of students' participating in continuing education. Participating students (n=69) worked as leaders in health care sector or aimed to become a leader in the future. The data was collected by a questionnaire between 10/2019 and 02/2020 and analyzed statistically.
Majority of the participants were women and worked as a nursing leader. The planning and management of human resources were emphasized in the participants' work descriptions. The strategic leadership as well as development of the operations, fnancial management and collaboration with the external stakeholders had lower emphasis in participants work descriptions. The clinical nursing and its development as well as communication and collaboration were emphasized in the participants' leadership skills. Participants considered their skills to be weakest in areas related to fnancial management and planning and marketing of services.
Based on the results, themes related to fnan-cial management, service planning and marketing, as well as strategic partnership should be considered in the development of continuous leadership education. Continuous education should be fexible and support students' diverse starting points and existing professional competences.